Increasing the effect of a remedial mathematics course by switching to an online format during the COVID-19 crisis: evidence from a German university. (10th September 2021) - Büchele, Stefan; Liebendörfer, Michael; Lankeit, Elisa
Abstract: Due to the COVID-19 crisis, many courses have been offered digitally. Using data from n = 1, 173 business students participating in a preparatory mathematics course at a German university that covered the same content as in 2018, 2019 and 2020, we examine how students' participation and the effect of the preparatory course changed. The data show that the participation rate has fallen slightly, but students' participation is rather similar to preceding years. Interestingly, students have participated more intensively. There are clear signs of dishonesty in the self-test (use of a calculator) and significant changes in predictors of performance. In particular, the effect of students' engagement in the course on their performance substantially increased. Further, we found a gender gap in performance affecting women. Finally, the data show that digital courses can be as effective as on-campus courses.